Detection of gynecological cancer and its treatment in the General Hospital Cayetano Heredia Base. Cayetano Heredia University - Arana, J. (2015)
A study of screening, treatment and monitoring of patients with gynecologic cancer is done from May 1969 to May 1971. A total of 92 cases of gynecological cancer was detected. Ancillary tests used for diagnosis indicated. You correspond to 77 cases of cervical carcinoma; 29 cases of cancer in situ, 6 microinvasive and 41 cases of invasive squamous cell cancer. Four cases of endometrial cancer, 10 cases of ovarian cancer and one case of vulvar cancer. Os therapeutic procedures is described in each case and evalúael monitoring.